Public-Private Management in the Urban Project "Ciudad Paraíso" in the City of Cali, Colombia - Díaz Mosquera, Carlos Andrés (Sociedad y Economía, 2023)
This article is the result of a study on the conformation of public-private management networks in the urban structuring of the central urban space of the city of Cali in the "Ciudad Paraíso" project. The methodology used consisted of a sociological analysis of the public and private institutional management networks in charge of the planning, administration and execution of the project. The research techniques implemented consisted of a review of the academic works published so far on the subject, analysis of local newspapers, interviews, institutional videos and virtual meetings. It is concluded that the management networks are mainly governed by urban discourses and practices such as Modernization, Development, Recovery and Refunctionalization of the downtown. In these networks and alliances, urban agents that are part of the public network of institutional management and potential investors predominate.